Islamic finance as a tool for achieving the Sustainable Development Goals (SDGs): Evidence from Nigeria - Yusuf, Jamiu Adeniyi; Ayuba, Ismail Aderole; Muhammed, Azeem Tunde (Journal of Islamic Economics Lariba, 2026)
IntroductionNigeria continues to face persistent development challenges, including infrastructure deficits, widespread poverty, financial exclusion, and increasing vulnerability to climate change. Conventional development financing sources such as tax revenues, foreign direct investment, and official development assistance remain insufficient to bridge the substantial financing gap required to achieve the Sustainable Development Goals (SDGs). This has renewed interest in alternative, ethical, and inclusive financing frameworks.ObjectivesThis study examines the role of Islamic finance as a complementary development financing mechanism for advancing the SDGs in Nigeria. Specifically, it evaluates the effectiveness of sovereign Sukuk in infrastructure development (SDG 9), Islamic social finance instrument, Zakat and Waqf in poverty alleviation and social welfare (SDGs 1, 2, 3, and 6), Islamic microfinance in financial inclusion (SDG 8), and Green Sukuk in climate action and renewable energy financing (SDGs 7 and 13).MethodThe study adopts a qualitative and analytical approach, drawing on a systematic review of post-2021 academic literature, policy reports, and institutional data. Descriptive and comparative analyses are complemented by case-based evidence from Nigeria, which has emerged as a regional hub for Islamic financial innovation.ResultsFindings indicate that Islamic finance instruments demonstrate strong alignment with sustainable development objectives through asset-backed financing, risk-sharing, and redistributive mechanisms. Nigeria’s experience with sovereign Sukuk illustrates improved project accountability and infrastructure delivery, while Zakat and Waqf contribute to community-level service provision. However, the scalability of Islamic finance across SSA is constrained by regulatory fragmentation, liquidity management challenges, low public awareness, and limited standardisation.ImplicationsPolicymakers in Nigeria and Sub-Saharan Africa should strengthen regulatory frameworks, improve standardisation, and promote public awareness of Islamic finance instruments to enhance their scalability and effectiveness as complementary financing mechanisms for achieving sustainable development goals.Originality/NoveltyThis study contributes to the literature by providing an integrated, instrument-specific assessment of Islamic finance and SDG implementation in SSA, offering policy-relevant insights grounded in recent empirical evidence.